Citifying Jesus: the making of an urban religion in the Roman Empire - Urciuoli, Emiliano Rubens (Wissenschaftliche Untersuchungen zum Neuen Testament, 2024)
Cover -- Title -- Acknowledgments -- Contents -- Citification of Religion: Studying Urban Religion Historically -- 1. An Urban Turn to "Lived Ancient Religion" -- 2. Integration and Differentiation: Urbanization via Religion -- 2.1. Worshipping and Settling Down: Religion at the Dawn of Urbanism -- 2.2. In the Wake of Fustel de Coulanges: Religion and the Making of Citizens -- 3. Another Story, A Different Concept: Citification of Religion -- 3.1. Spatializing "Lived Religion" Within, Beyond, and After the Polis -- 3.2. Citification as Aspiration -- 3.3. Citification as Adaptation (and Appropriation) -- 3.4. Citification of Religion: A Definition -- 4. Citifying Jesus: Christ Religion as a Case Study -- 4.1. Between Empire and Countryside: Revising the "Urban Thesis" -- 4.2. Neither Global Nor Local: Beyond the "City-by-City" Approach -- 4.3. No Exit from the Urban -- 4.4. Citifying Jesus in a Rural Empire -- 4.4.1. A Biased Dataset -- 4.4.2. An Ideal Subject -- 4.5. Nine Trajectories of Citification: Overview of Chapters -- I. Jumping Among the Temples: Against the Polytheists'"Spatial Fix" -- 1. Gluing Gods to Places: From Carthage to Çatalhöyük and Back -- 2. Religion and the "Spatial Fix" -- 3. No Rescue in the Fix: The Critical Sacred Geography of the Early Christians -- 3.1. Immaterial Religion -- 3.2. Good and Evil Investments -- 3.3. Starving the (Urban Religious) Beast -- 3.4. A Nonsense Parceling Out of Space -- 4. Conclusion: Jumping Among the Basilicas -- II. An Archetypal Blasé? Justin Martyr, the Metropolitan Man, and the Segmentation of Urban Life -- 1. Plunging Simmel into the Mediterranean World -- 2. Coping with Rome: The Mental Life of Justin of Neapolis -- 2.1. How Did the Metropolis Affect Justin as a Christ Believer? -- 2.2. How Did the Metropolis Affect Justin as a Teacher?.